Community Structure of Decapods in the Coastal Waters of Rupat Utara District - M. Aqbal Firmandika; Syafruddin Nasution; Zulkifli Zulkifli (Tropical Marine Enviromental Sciences, 2024)
Decapods are one of the macrozoobenthos consisting of the Taxonomy of the last five pairs of the eight thoracic appendages. This study aimed to determine the structure of the decapod community in the waters of Rupat Utara District Beach, including abundance, diversity, uniformity, dominance index, distribution pattern, and community similarity index in Rupat Utara waters. The survey method was used in the study. Determination of observation stations was carried out purposively. The species found consisted of 8 (eight) species from Rupat Utara waters. The abundance of decapods was 1,326 ind/Ha. The diversity index value (H'= 1.48) is included in the medium category. The value of the uniformity index (E = 0.83) is included in the high category. The dominance index (C = 0.31) and similarity index of decapod community I to II is 83%, I to III 77%, and II to III 93%.